Die Verlagerung hochrangiger Dienstleistungen aus der Innenstadt von Bogotá/Kolumbien: Etappen - Parameter - Auswirkungen - Mertins, Günter; Müller, Jan Marco (ERDKUNDE, 2000)
In the thirties the growth of population and area of Latin American cities, or rather metropolises, had started off. From 1950 on it has increased strongly. In parallel with that, a city expansion took place almost everywhere along the arterial roads leading towards the new districts of the higher class. A short time later a relocation of higher public and private services set in from the old parts of town to locations which are increasingly remote from the inner cities, namely along those axes of growth. There, new high service areas or even CBDs develop. At the same time this was linked to a degradation of the architectural fabric as well as the function of the former city centres. In this paper, these generally known processes (Griffin a. Ford 1983; Bähr u. Mertins 1995) will be examined, presented and interpreted in detail for Bogotá. The two figures clearly show on the one hand the step-by-step relocation of high order services combined with a CBD migration spreading to the north of the city from 1947 to 1997, and on the other hand the change of function of the former main shopping street between 1947 and 1997. Concerning Bogotá it can be shown that, in comparison with other cities in Latin America, the development and expansion of the CBDs started off relatively late (after 1945/50) but then progressed rapidly. However, after a quite short period of leadership (of about 15 to 20 years), the main shopping street soon lost its significance, a development which was connected with increasing problems of insecurity, cramped spatial conditions, etc.. The development and rapid growth of new CBDs of international standard in the north of the city accelerate the relocation of high order services including banking centres, which have still remained in the inner city. Finally, the question is raised whether - in analogy with the theory of the product life cycle - a certain functional cycle (growth, maturity and decline phase) exists for CBDs. The findings for Bogotá as well as for other Latin American metropolises suggest that.